Identification of B Cell and T Cell Epitopes Using Synthetic Peptide Combinatorial Libraries. Issue 3 (8th March 2022) - Pinilla, Clemencia; Giulianotti, Marc A.; Santos, Radleigh G.; Houghten, Richard A.
Abstract: This article presents a combinatorial library method that consists of the synthesis and screening of mixture‐based synthetic combinatorial libraries of peptide molecules to identify B and T cell epitopes. The protocols employ peptide libraries to identify peptides recognized by MAbs and T cells. The first protocol uses a positional scanning peptide library made up of hexapeptides to identify antigenic determinants recognized by MAbs. The 120 mixtures in the hexapeptide library are tested for their inhibitory activity in a competitive ELISA. The second protocol uses a decapeptide library to identify T cell peptide ligands. The 200 mixtures of the decapeptide library are tested for their ability to induce T cell activation. Support protocols cover optimization of the assay conditions for each MAb or T cell, to achieve the best level of sensitivity and reproducibility, and preparation of a hexapeptide library, along with deconvolution approaches. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Screening peptide library for antibody inhibition Basic Protocol 2 : Screening a peptide library to identify CD4 + Or CD8 + T cell ligands Support Protocol 1 : Optimizing antigen and antibody concentrations for screening assay Support Protocol 2 : Preparing a positional scanning peptide library